The Implicit Component of Moral Disengagement: Applying the Relational Responding Task to Investigate Its Relationship With Cheating Behavior. (January 2022) - Fida, R.; Ghezzi, V.; Paciello, M.; Tramontano, C.; Dentale, F.; Barbaranelli, C.
This article aims to conceptualize, for the first time, an implicit form of moral disengagement and investigate its role in relation to cheating behavior. In line with the implicit social-cognition models, we argue that the implicit moral disengagement would represent an unintentional, automatic, and less accessible form of the mechanisms bypassing the moral self-regulatory system. We anticipate that in situations implying on-the-spot decisions and where individuals might suffer no consequences for the misconduct, the implicit moral disengagement would predict the actual behavior while the explicit moral disengagement would predict self-reported conduct. The results of three empirical studies provide support for the theorization of an implicit moral disengagement and its assessment through a newly developed implicit measurement procedure using the relational responding task. Results of the structural equation models, including both implicit and explicit moral disengagement, demonstrated that only the implicit one was associated with the actual misconduct.